Functionalization of citric acid-based carbon dots by imidazole toward novel green corrosion inhibitor for carbon steel. (20th August 2019) - Yang, Dongping; Ye, Yuwei; Su, Yue; Liu, Shuang; Gong, Dirong; Zhao, Haichao
Abstract: In order to address the environment pollution problem in the cleaning process of metal, a green corrosion inhibitor with the size of 3–5.5 nm was synthesized from imidazole ionic liquids and citric acid-based carbon dots. The inhibition behaviors of this inhibitor for Q235 steel in 1 M HCl and 3.5 wt% NaCl solutions were studied by electrochemical measurement, surface analysis and weight loss. The dependence of corrosion current density and impedance modulus of Q235 steel on the different concentrations of corrosion inhibitor solutions showed that the as-prepared inhibitor presented a valid protective effect on steel in both corrosive solutions. In the meantime, the inhibition efficiency of steel in 1 M HCl solution was higher than that in 3.5 wt% NaCl solution. The mechanism of corrosion inhibitor was discussed with isothermal adsorption model. The result revealed that the Langmuir adsorption was followed and the mechanism was physicochemical adsorption in these two solutions. Graphical abstract: Image 1 Highlights: We obtained green functionalization of citric acid-based carbon dot by imidazole. Inhibition property of steel in HCl and NaCl solution with inhibitor was high. Absorption mechanism of inhibitor on steel surface was physicochemical adsorption.